COMPUTE-COMMUNICATE CONTINUUM TECHNOLOGY (2017)
The present disclosure relates to Compute-Communicate Continuum ("CCC") technology, which challenges today's use model of Computing and Communications as independent but interfacing entities. CCC technology conflates computing and communications to create a new breed of device. Compute-Communicate Continuum metal algorithms allow a software programmer to compile/link/load and run his software application directly on device hardware providing Super Computing and Extreme Low Latency links for demanding financial applications and other applications. CCC based multiple CCC-DEVICE hardware platforms can be interconnected using its ELL "Metal Shared Memory Interconnects" form what looks like a "single" machine that crosses different geographies, asset classes, and trading venues. Thus, the technology enables the creation of a new category of Compute-Communicate devices (CCC-DEVICE Series appliances) that can connect multiple geographically distributed locations with extreme low latency and provide supercomputing for distributed data using High Performance Embedded Computing (HPEC) and Extreme Low Latency (ELL) Communications.